2019
DOI: 10.1145/3364204
|View full text |Cite
|
Sign up to set email alerts
|

The Mobile Server Problem

Abstract: We introduce the Mobile Server problem, inspired by current trends to move computational tasks from cloud structures to multiple devices close to the end user. An example of this is embedded systems in autonomous cars that communicate to coordinate their actions. Our model is a variant of the classical Page Migration problem. More formally, we consider a mobile server holding a data page. The server can move in the Euclidean space (of arbitrary dimension). In every round, requests for da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…In [12] it was already shown that no online algorithm for our problem can be competitive even on the real line and with just k = 1 server. As a consequence, we employ the following methods to derive bounds independent of the number of requests for the problem: On the one hand we apply resource augmentation as in [12]: i.e., we allow the online algorithm to use a maximum movement distance of (1 + δ)m s . Other than in the case of k = 1, this is not enough to receive algorithms with a competitive ratio independent of time.…”
Section: Our Results and Outline Of The Papermentioning
confidence: 98%
See 4 more Smart Citations
“…In [12] it was already shown that no online algorithm for our problem can be competitive even on the real line and with just k = 1 server. As a consequence, we employ the following methods to derive bounds independent of the number of requests for the problem: On the one hand we apply resource augmentation as in [12]: i.e., we allow the online algorithm to use a maximum movement distance of (1 + δ)m s . Other than in the case of k = 1, this is not enough to receive algorithms with a competitive ratio independent of time.…”
Section: Our Results and Outline Of The Papermentioning
confidence: 98%
“…We show that, for k ≥ 2, both methods are needed to yield competitive bounds independent of the length of the instance. For k = 1, it was shown in [12] that a locality of requests can improve the competitiveness, but is not necessary to achieve a constant upper bound.…”
Section: Our Results and Outline Of The Papermentioning
confidence: 99%
See 3 more Smart Citations